The Use of Roleplay and Narrative Text to Teach Speaking Skill - Yolanda Sela Amelia; Yuliyanto Sabat; Lailatul Musyarofah (Journal of English Language and Education, 2026)
Speaking is a fundamental component of English language learning as it enables learners to communicate effectively in both academic and real-life contexts. Nevertheless, many EFL students continue to experience difficulties in developing speaking proficiency due to limited vocabulary, lack of self-confidence, grammatical inaccuracies, and speaking anxiety. Although role-play has been widely acknowledged as an effective instructional technique for improving speaking skills, research examining its integration with narrative texts remains relatively limited. Therefore, this study aims to describe the implementation of role-play through narrative texts in teaching speaking skills and to explore students’ perceptions of its use in the classroom. This study employed a descriptive qualitative approach, with data collected through classroom observations and semi-structured interviews involving eleventh-grade Hospitality students at SMKN 8 Surabaya. The findings indicate that narrative text-based role-play promoted students’ confidence, active participation, speaking fluency, and comprehension of narrative texts. Although students encountered challenges related to vocabulary, grammar, pronunciation, and speaking anxiety, continuous teacher guidance and feedback helped them address these difficulties. These findings suggest that integrating role-play with narrative texts is an effective pedagogical strategy for enhancing EFL students’ speaking skills while fostering greater engagement and confidence in classroom communication.